Modeliranje onesnaževanja mehiških lagun s poljedelskih površin - prvi del: metodologija - Četina, Matjaž (Acta hydrotechnica, 2002)
Many coastal lagoons in Mexico are used for mariculture (fish, shrimps, oysters). Regions near lagoons are usually exploited by agriculture and drain water from this area brings nutrients and pesticides into the lagoons. By means of both models and some measurements, an optimum scenario of agricultural management will be proposed. This paper describes the proposed methodology, the second part will describe in detail the hydrodynamic and pollutant transport simulations for the case study of the Carizo valley in NW Mexico, and the third part will deal with modelling of agricultural pollution by the GLEAMS model and proposed management for the same case study.
Keywords: coastal lagoons; dvodimenzijsko hidrodinamično modeliranje; GLEAMS model; mariculture; marikultura; Mehika; Mexico; model GLEAMS; modeliranje polutantov; modelling of pollutants; obalne lagune; twodimensional hydrodynamic modelling